RANCANG BANGUN DAN VALIDASI PERANGKAT EKSPERIMEN FLUIDA DINAMIS SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Mariyo, Hadis; ', Zulhelmi; Sudrajad, Hendar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research was to develop are equipment of dynamics fluid experiment as physics teaching and learning media, resulting in a viable and valid device used as a media of instruction. The subject of this research was an experiment equipment consist of experiment tool and guided book. Data was collected by using assessment sheets of validation that has been given to validators, in which 3 validators were lecturers as expert and 2 validators were physics teachers. The data was analyzed descriptively to find index of validity of experiment equipment. We found that experiment equipment validation was 3,46 with the very high category and experiment guided book with validation was 3,6 with the very high category. Based on the data analysis we have been concluded that an experiment equipment of dynamics fuid as the media in learning physics at SMA can be said valid with the very high category and feasible to be done trial at school.Keyword: Validation, Experiment equitment, Dynamics Fluid.